The Stability of Factor IX Concentrate During Storage - Suomela, H; Vahtera, Elina (Thrombosis and Haemostasis, 1982)
A storage study of factor IX concentrate was performed on 35 randomly selected batches that had been prepared between 1976 and 1980. Vacuum stability, dissolution time, F IX procoagulant activity, NAPTT, and thrombin generation were measured immediately after the manufacturing process and compared in this study with the results obtained from the spare samples analysed in 1981. No significant changes during storage at cold room temperature for up to 5 years were established. The product can thus be considered to be stable for 5 years at + 4° C.
Keywords: Factor IX concentrate; Stability; Shelf life; Thrombogenicity; Thrombin generation